Protection of Intellectual Property in the Academy: Case Study of UnB Gama University - Godinho, Larissa da Costa e Silva (2018)
The objective of this article is to contribute to a deeper understanding of the registration of intellectual property in the academy, based on the case study of the UnB Gama College (FGA). The analysis is based on the protection statistics of trademarks, industrial designs, softwares and patents developed at the institution, obtained through searches on the National Institute of Industrial Property (INPI) (of Brazil) website, as well an interview with the team of the Technological Protection sector of University of Brasilia Technological Development Support Center (CDT/UnB). The results showed that FGA occupies a prominent position in the area of intellectual property protection in University of Brasilia. However, the study main conclusion is that the numbers of records are not significant if we consider the great technological potential that this campus has.